2017
DOI: 10.1007/s12640-017-9709-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Alteration of [3H]Glucose Uptake in Wistar Rat Brain and Peripheral Tissues

Abstract: The present study was designed to investigate the role of postnatal fluoride intake on [3H]glucose uptake and transport in rat brain and peripheral tissues. Sodium fluoride (NaF) in a concentration of 10 or 50 ppm was added to the drinking water of adult Wistar rats. The control group received distilled water. After 4 weeks, respective plasma fluoride levels were 0.0541 ± 0.0135 μg/ml (control), 0.0596 ± 0.0202 μg/ml (10 ppm), and 0.0823 ± 0.0199 μg/ml (50 ppm). Although plasma glucose levels were not altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…These observations suggest that fluoride inhibits the transport of nutrients. Several previous reports found that fluoride can inhibit glucose import. We tested for Pho87p/Pho90p inhibition by monitoring phosphate uptake under increasing fluoride (Figure A). Simultaneous addition of fluoride with phosphate showed no detectable difference in phosphate uptake.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that fluoride inhibits the transport of nutrients. Several previous reports found that fluoride can inhibit glucose import. We tested for Pho87p/Pho90p inhibition by monitoring phosphate uptake under increasing fluoride (Figure A). Simultaneous addition of fluoride with phosphate showed no detectable difference in phosphate uptake.…”
Section: Resultsmentioning
confidence: 99%
“…A significant effect of F on OC expression has been found to occur in adults at serum F levels of 1.0 μM [154] or when urinary F levels exceed 0.62 mg/L in adolescent children [155]. Consistent with this data, several in-vivo studies have reported that chronic F exposure enhances plasma insulin levels and promotes insulin resistance in rodents [211,212,213,214,215]. A similar association has also been found in humans chronically exposed to F [216].…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 77%
“…Fluoride exposure may be associated with changes in the profile of proteins involved in energy metabolism [ 64 ], and researchers have suggested that impaired glucose metabolism in neurons is correlated with decreased expression of the GLUT-1 transporter [ 65 ]. On the other hand, increased glucose transport into brain cells has also been documented, although without changes in transporter expression, suggesting a compensatory mechanism in response to damage [ 66 ]. Chronic fluoride exposure also affects amino acid and lipid metabolism [ 61 , 67 ].…”
Section: Fluoride As An Environmental Toxinmentioning
confidence: 99%
“…Studies in rats have shown that NaF decreases the expression of GLUT1, a glucose transporter in the brain, but the results of the few existing studies are conflicting. Some point to decreased expression of the GLUT1 glucose transporter and reduced glucose uptake into the brain [ 65 ], while others report compensatory increases in glucose uptake in the brain and peripheral tissues without significant changes in GLUT1 and GLUT3 expression [ 66 ]. Due to the paucity of data on the molecular mechanism underlying the effects of fluoride on brain glucose uptake, transport, and metabolism, it is difficult to clearly assess its role in glioma progression and invasiveness.…”
Section: Glial Defence Mechanisms Against Metabolic Stress (Glucose)mentioning
confidence: 99%